Pathogens crossing borders: global animal diseases and international responses, 1860-1947 - Knab, Cornelia (Routledge studies in the history of science, technology and medicine, 2022)
Animal diseases and the global 19th century -- International approaches to contain cross-border epizootics, 1863-1914 -- Restarting veterinary internationalism after the First World War -- The League of Nations and international projects addressing animal diseases -- Veterinary internationalism in times of crisis : the OIE, 1927-1947.
Keywords: Geschichte 1860-1947; Hochschulschrift